Une nouvelle procédure d’expérimentation comportementale à l’interface entre les approches « Naturalistes » et « Généralistes » de la cognition du primate - Joël Fagot (Revue de Primatologie)
The study of primate cognition may adhere to two different paradigms. The first one is referred to as the Naturalist approach. Investigators in that field attempt to characterize natural behaviors, and to identify the various factors accounting for their evolution in nature.   The second one is referred to as the Generalist approach. Generalist researchers attempt to identify cognitive processes shared by animals and humans. While Naturalist researchers prefer natural or semi-natural conditions for their science, the context favored by the Generalist researchers is the laboratory allowing the test of isolated primates. In that paper, I present a novel experimental protocol favoring an interface between the Naturalist and Generalist approaches. The general idea of this protocol is to present a laboratory nearby an enclosure where monkeys live in a semi-natural context. The test systems installed within the laboratory are opened and freely accessible from the enclosure. The monkeys (baboons in our research) can voluntarily enter the test booth to participate to the research. This protocol has been fully developed, installed and validated in my laboratory during the last 3 years, and I present here the main results collected during that period. I (1) demonstrate that this approach allows the test of a large number of participants which participate to the research at a high frequency, (2) identify the main factors (age, day time, reinforcement rate, etc..) that affect their behavior in the tasks, (3) illustrate the effect of the test systems on the spontaneous behavior of the monkeys, and (4) briefly present two studies that used this method, in order to illustrate its potential for the Generalist and Naturalist research programs.